KARAKTERISASI RASA GURIH PADA BEBERAPA PRODUK PANGAN (Characterisation of ‘Gurih’ Taste of Several Food Products) - Nadia, Lula; Apriyantono, Anton; Rahayu, Winiati Puji (Jurnal Matematika Sains dan Teknologi, 2004)
The aim of this research was to find the sensory characteristic of ‘gurih’ taste of some food models. Several steps were used to determine: (1) People perception of ‘gurih’, (2) Food ingredients which influence ‘gurih’ taste intensity, and (3) The difference between ‘gurih’ and umami taste. From 1500, 908 questionnaires were returned with complete answer by the participants. Meat, peanut and cheese were chosen as being ‘gurih’ food by 97% of participants. They also perceived that ‘gurih’ taste present in food actually by the contribution of several food ingredients mainly protein, fat, and salt. Use of oil was preferred by 100% of the participants as a type of cooking which could build ‘gurih’ taste in food. Based on participants choice of ‘gurih’ food, meat, peanut and cheese were used as food models. Meat model was made by using hydrolyzed vegetable protein (HVP), chicken fat, and chicken flavor (22.0 : 6.2 : 0.5), peanut model was made by using HVP, peanut oil, corn starch, and carboxy methyl cellulose  (27.5 : 42.5 : 20.0 : 2.8); and cheese model was made by using skim milk, milk fat, salt, and cheese flavor (27.5 : 18.0 : 3.2 : 0.5). Using Omission Test for each compound of food model ingredient and t-test to compare the ‘gurih’ level of meat or peanut model, it was found that omitting  HVP, salt and chicken fat or peanut oil gave significant lower level of ‘gurih’ of the models than the complete one (p < 0.01). The same result was also found in cheese model, where omitting skim milk, milk fat or salt gave significant lower level of ‘gurih’ of the model than the complete one.  It was also found that the omission of protein-rich ingredient (HVP or skim milk) and salt gave significantly lower level of ‘gurih’ taste than the omission of chicken fat, milk fat or peanut oil (p < 0.01). Using the concentration which give 10% stimulus, the intensity of ‘gurih’ taste of food models (0.5% w/v for meat, 0.1% w/v for peanut, and 1% w/v for cheese) was significantly higher than umamis’ models (0.06% w/v for MSG, 0.03 : 0.17 w/v for MSG + salt, 0.03 : 0.17 : 0.11 w/v) (p < 0.01) and was the same with umamis’ models MSG + salt + oil or fat. This finding indicates that the addition of fat was importance to make ‘gurih’ taste to the both model. Meanwhile, there were no research was found that tells the influence of fat on umami taste. In conclusion, ‘gurih’ taste could be found mainly in meat, peanut, and cheese. ‘Gurih’ taste intensity was influenced by several food ingredients. The presence of ‘gurih’ taste was easy to be recognized in food models and the addition of fat in the model make ‘gurih’ taste probably has different taste  from umami.